The reassessment of personal competencies in human resources management and in business-oriented higher education - Varga, Erika; Boda, Helga; Bárdos, Kinga Ilona (Studia Mundi – Economica, 2016)
The timeliness of our topic is proved by the fact that nowadays human resources play an indispensable part in the resource system of economic organizations. Our paper examines the personal competencies that play a vital role in corporate efficiency, competitiveness and success. Moreover, we also illustrate how this role has been changing in time. One of the objectives was to create and test a competency structure tailored to the Hungarian labour market situation.
Keywords: (personal) competencies; labour market; higher education